Almal kom na Lubbe" : die skoenmakerverhaal van A.P. Lubbe en Seun (Edms.) Bpk. 1918-2001 - Van Eeden, Suzanne (Stellenbosch : University of Stellenbosch, 2008)
Thesis ( MA (History))--University of Stellenbosch, 2007.